Analysis of Tax Aggressiveness on the Consumer Non-Cyclicals, Property and Real Estate Sector Companies in the Indonesia Stock Exchange, 2018-2019 - Firda Nurfazriati Ma’mudah; Achmad Fauzi; Mardi Mardi; Dwi Kismayanti Respati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the tax aggressiveness influenced by Leverage, Capital Intensity and Inventory Intensity in consumer non-cyclicals, property and real estate sector companies on the Indonesia Stock Exchange for the 2018-2019 period. Using descriptive quantitative method, and a sample of 72 companies, the data were analyzed by multiple linear regression, t and F statistic tests and and coefficient of determination. The results of hypothesis testing are that leverage has a significant positive effect on tax aggressiveness capital intensity has a significant positive effect on tax aggressiveness, while inventory intensity has a significant negative effect on tax aggressiveness. Simultaneously leverage, capital intensity and inventory intensity have a significant effect on tax aggressiveness leverage effect, capital intensity and inventory intensity on tax aggressiveness is 44.9% and the remaining 55.1% is influenced by other factors that have not been studied. It is suggested that the next research uses other sector companies and enlarges the number of samples, and uses CSR, liquidity, profitability variables to influence the company's tax aggressiveness. This research can be used as information for potential investors to carefully invest the company's capital.